2015
DOI: 10.1007/s12374-015-0105-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Squamosa Promoter Binding Protein-LIKE genes in wheat

Abstract: Common wheat (Triticum aestivum) is an allohexaploid (AABBDD), with Triticum urartu (AA) and Aegilops tauschii (DD) as its A and D genome donors. Squamosa Promoter Binding Protein-Like (SPL) genes play important roles in plant development; however, a systematic study of this gene family in wheat is still lacking. Here, we mined the wheat genomes for SPLs and found 19 SPL genes each from the T. urartu and Ae. tauschii genomes. We also identified 58 SPL genes from the hexaploid wheat genome. We then compared the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 55 publications
3
22
0
Order By: Relevance
“…46) The SBP domain can combine with the cis-element TNCGTACAA, for which GTAC is the essential core sequence. 47) In wheat, 1365 TFBSs were detected in the non-coding regions of fl-cDNAs (Table 1), and the cis-element containing TNCGTA-CAA was confirmed in wheat (S2 File).…”
Section: Discussionmentioning
confidence: 94%
“…46) The SBP domain can combine with the cis-element TNCGTACAA, for which GTAC is the essential core sequence. 47) In wheat, 1365 TFBSs were detected in the non-coding regions of fl-cDNAs (Table 1), and the cis-element containing TNCGTA-CAA was confirmed in wheat (S2 File).…”
Section: Discussionmentioning
confidence: 94%
“…However, even though a little characterization of wheat SBP (TaSBP) family has been done, more is needed [37,38]. In 2015, Wang et al, using common wheat and the genome database of its A and D subgenome donors Triticum urartu L. (AA) and Aegilops tauschii L. (DD), conducted a whole-genome analysis of the wheat SBP family [39]. Compared with the 19 SPL genes present in rice, Wang et al found 13 and 7 complete open reading frames (ORFs) from wheat diploid progenitors Aegilops tauschii L. (DD) and Triticum urartu L. (AA), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In rice, OsSPL13 positively regulates cell size in the grain hull resulting in enhanced grain length and yield (Si et al, 2016); OsSPL14 regulates plant architecture by controlling shoot branching during vegetative growth and panicle development (Jiao et al, 2010;Miura et al, 2010); and overexpression of OsSPL16 promoted cell proliferation and grain filling, resulting in increased grain width and yield (Wang et al, 2012). However, apart from bioinformatics and gene expression information (Zhang et al, 2014a;Wang et al, 2015), very little is known about the biological functions of SBP-box family members in common wheat. Ten wheat TaSPL genes have been cloned and classified into five groups (G1-G5; Zhang et al, 2014a).…”
mentioning
confidence: 99%